The application of foraminifera to reconstruct the rate of 20th century sea level rise, Morbihan Golfe, Brittany, France - Rossi, V.; Horton, B. P.; Corbett, D. R.; Leorri, E.; Perez-Belmonte, L.; Douglas, B. C. (Quaternary Research, 2011)
Foraminiferal assemblages preserved within salt-marsh sediment can provide an accurate and precise means to reconstruct relative sea level due to a strong relationship with elevation, which can be quantified using a transfer function. We collected a set of surface samples from two salt marshes in the Morbihan Golfe, France to determine foraminiferal distribution patterns. Dominant taxa included Jadammina macrescens, Trochammina inflata, Haplophragmoides spp. and Miliammina fusca. We developed a foraminifera-based transfer function using a modern training set of 36 samples and 23 species. The strong relationship between observed and predicted values (r(jack)(2) = 0.7) indicated that foraminiferal distribution is primarily controlled by elevation with respect to the tidal frame and precise reconstructions of former sea level are possible (RMSEP(jack) = 0.07 m). The application of the transfer function to a short salt-marsh core (0.32 m) allowed the reconstruction of former sea levels, which were placed in a chronological framework using short-lived radionuclides ((210)Pb and (137)Cs). The agreement between the foraminifera-based sea level curve and the Brest tide-gauge record confirms the reliability of transfer function estimates and the validity of this methodology to extend sea level reconstructions back into the pre-instrumental period. Both instrumental and microfossil records suggest an acceleration of sea level rise during the 20th century. (C) 2010 University of Washington. Published by Elsevier Inc. All rights reserved.
id: 1889; 713FR Times Cited:1 Cited References Count:71submittedY